Perception of Transformational Leadership and Commitment on Employee Performance - Harnida W. Adda; Pricylia Chintya Dewi Buntuang; Salma D (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Employee performance is the center of attention in all government agencies. Employee performance can be influenced by many variables such as leadership and commitment. This study aims to determine the effect of transformational leadership and commitment on the performance of the employees of the Regional Fisheries Office of Morowali District, Central Sulawesi Province. This study used quantitative methods. The population of this study was all employees of the Regional Fisheries Office of Morowali District with a total of 87 employees. The sample was determined with a census sampling technique so that all populations were sampled. Data were collected from observation, questionnaires, and written documents. Then, the data were analyzed using descriptive statistics and multiple linear regression to test the research hypotheses. The results showed that transformational leadership and commitment greatly affect the employee performance of the Regional Fisheries Office of Morowali District. The results of descriptive statistics showed that the leaders in the Regional Fisheries Office of Morowali District have a clear vision and mission; show an optimistic attitude; and can stimulate subordinates to be creative. Meanwhile, the leaders never openly corrected or criticized their subordinates. It has a low response because of the leader's closed attitude towards subordinates, especially in providing corrections and criticism. In terms of commitment, employees at this office feel that they have a high emotional bond with the organization. However, they easily leave the office as they think that what they are doing is less valuable.